Commercialization of Handicraft Products from Water Hyacinth in Aren Handicrafts - Ifa, Khoirul; Meilan, Ria; Yulianti, Ani (IMPOWERMENT SOCIETY, 2023)
The superior product of Aren Handicraft is a product made from water hyacinth which has not been commercialized in the market and is not well known by the public, therefore this product needs to carry out product commercialization with innovation and promotion. The objectives of this activity are: online promotional assistance through social media and e-commerce and product innovation assistance, through the creation of unique and attractive new products. The approach methods offered to solve partner problems consist of surveys, interviews, online promotion assistance, product innovation assistance, monitoring and evaluation. Based on the results of the PKM implementation, several informants said that the product was quite interesting because there were not many businesses that could make handicrafts made from water hyacinth. The business capital is IDR 5,000,000. The price of the product depends on the type of product, baskets of water hyacinth are priced at 55,000-65,000 while palcemates cost 24,000-30,000. The marketing area for water hyacinth products is the local area of Jember, namely the area around the sub-districts of Bangsalsari, Umbulsari, Balung, Puger and its surroundings. The scope of online marketing covers all regions of Indonesia. Promotion through online media such as Instagram, TikTok, website and marketplace Shopee, Bukalapak. The form of product innovation from Aren Handicraft varies from new product innovations such as tissue holders and several products to photo props and hampers.